2014
DOI: 10.1371/journal.pone.0107489
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Recovery Rate in the Photocycle of the Bacterial Photoreceptor YtvA Is Affected by the Cellular Environment and by Hydration

Abstract: We report thermal recovery kinetics of the lit state into the parental dark state, measured for the blue light-sensing photoreceptor YtvA inside overexpressing E. coli and B. subtilis bacterial cells, performed for the wild type and several mutated proteins. Recovery was followed as a recovery of the fluorescence, as this property is only found for the parental but not for the photochemically generated lit state. When cells were deposited onto a microscope glass plate, the observed thermal recovery rate in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 43 publications
(77 reference statements)
2
28
0
Order By: Relevance
“…The recovery kinetics of the photocycle in YtvA has been measured to understand the molecular basis for the propagation of photosignals in light-sensing proteins. 32,38,39 The dark regeneration kinetics of YtvA-LOV from the lightactivated state to the dark-ground state was known to be slower than the value of the full-length YtvA protein in the previous work. 30 Raffelberg et al suggested that the mutations of hydrogen-bond network residues (N94S, N94A, and Q123N) accelerated the recovery kinetics.…”
Section: Fluorescence Spectroscopymentioning
confidence: 92%
“…The recovery kinetics of the photocycle in YtvA has been measured to understand the molecular basis for the propagation of photosignals in light-sensing proteins. 32,38,39 The dark regeneration kinetics of YtvA-LOV from the lightactivated state to the dark-ground state was known to be slower than the value of the full-length YtvA protein in the previous work. 30 Raffelberg et al suggested that the mutations of hydrogen-bond network residues (N94S, N94A, and Q123N) accelerated the recovery kinetics.…”
Section: Fluorescence Spectroscopymentioning
confidence: 92%
“…It carries a LOV (light, oxygen and voltage) domain and a STAS (sulphate transporters and antisigma‐factor antagonists) domain and binds FMN (flavin mononucleotide) as a chromophore. Its cycle of activation by light/recovery is also tuned to the environment by features such as hydration (Pennacchietti et al ., 2014). Sensing light is a way for cells to tell immediately where they are located.…”
Section: Bacillus Subtilis In 2017mentioning
confidence: 99%
“…The dark adapted state LOV 450 , brightly fluorescent with Φ F ca. 0.2–0.3 can be switched by BL (blue arrow) to generate the covalent FMN‐Cys adduct LOV 390 that thermally recovers (black arrow) to LOV 450 on a highly variable time‐scale (from seconds to days at room temperature, depending on the specific protein and on the microenvironment) . Formation of LOV 390 normally occurs via the decay of a flavin triplet state (not shown), possibly involving a flavin‐cys radical pair .…”
Section: Introductionmentioning
confidence: 99%
“…Some details of the photochemical events still remain to be clarified, e.g. the involvement of a flavin radical species , as well as factors that control the dynamics of the photocycle in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation